Food Matters : all you need is the lavatory 2. - El Khadaroui, Samira; Van, Laura ([S.l.] : CROX 580, 2018)
Daem, Aaron ; Verhaegen, Hans ; Goossens, Antoine ; Van Roey, Emma ; Astridcollectief ; Westphal, Sarah ; De Clercq, Bart ; Doubrawa, Reinhard ; Maris, Bart ; Lezaire, Christophe ; Felix, Benoit ; Morrens, Peter ; Borloo, Bram ; Mabesoone, Melissa ; Van Stappen, Bram ; Pauwels, Bjorn & Dedecker, Nora ; Lemmens, Kristof ; Bogaert, Dirk ; Geurts, Frederic ; Zoete, Dirk ; Ronse, Elien ; Lutgens, William Ludwig ; De Vlam, Emilie ; Van de Casteele, Merel ; Van de Velde, Griet ; Pevernagie, Renée ; Marijnissen, Geert ; Van Roy, Maarten ; Van Dorpe, Stijn ; Zeghers, Janes ; De Clercq, Pieter ; Frateur, Jeroen ; Le Thi Thu, Thuy & De Geyter, Thomas ; Cremers, Jesse ; Mabesoone, Natasja ; De Wilde, Johan ; Vermeren, Karen ; De Corte, Katelijne ; Vanhee, Klaas ; Vande Veire, Maud ; Paridaen, Merlyn ; Eckes, Sacha ; Van Cauter, Steffie
FOOD MATTERS. all you need is the lavatory 2, Coproductie croxhapox & de vloer, Gent, 30 november - 29 december 2018
boek